Prerequisites for accelerated aging of transformer oil: A review - Zainuddin, Hidayat; Othman, Nur Amirah; Yahaya, Muhammad Sharil; Azis, Norhafiz; Ibrahim, Zulkifli (IEEE, 2025)
The oil-paper insulation system is a critical component that serves excellent insulation properties in a power transformer. It has high dielectric strength that can withstand high voltages during operation. However, both insulation materials will slowly degrade in long-term operation, which can cause serious deterioration to the performance of the insulation system in the power transformer. Numerous researchers have used accelerated aging tests under laboratory conditions in order to simulate the degradation conditions in oil-filled transformers. This approach can shorten the lifetime of an electrical insulation system, allowing for investigation of the behavior of the insulation material and the prediction of the insulation system’s lifespan in power transformers. This article focuses on a comprehensive review of the accelerated aging procedure under laboratory conditions, which includes five crucial elements that need to be considered prior to the aging experiment. These elements include the pretreatment of insulating liquids, pretreatment of cellulose papers, preparation of metal catalysts, selection of appropriate aging temperature, and determination of the time period for accelerated aging. This review article will provide helpful pointers to researchers engaged in accelerated aging in laboratory conditions.